2014
DOI: 10.1007/s11250-014-0692-4
|View full text |Cite
|
Sign up to set email alerts
|

HSP70 as a marker of heat and humidity stress in Tarai buffalo

Abstract: Heat and humidity stress is a constant challenge to buffalo rearing under tropical climatic conditions. Heat shock proteins (HSPs) constitute a ubiquitous class of highly conserved proteins that contribute to cell survival during different conditions of stress. The present study was carried out in Tarai buffaloes to study the expression of HSP70 in their peripheral blood mononuclear cells during different seasons and establish it as a marker of heat and humidity stress in buffaloes. Blood samples were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 22 publications
4
35
0
Order By: Relevance
“…Buffaloes are more predisposed to heat stress than cattle (Manjari et al 2015). The cellular function in various tissues of the female reproductive tract, including the follicle, oocyte and embryo can be affected by hyperthermia (Hansen 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Buffaloes are more predisposed to heat stress than cattle (Manjari et al 2015). The cellular function in various tissues of the female reproductive tract, including the follicle, oocyte and embryo can be affected by hyperthermia (Hansen 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the influence of seasonal changes as identified by Fader et al (1994) and Manjari et al (2015), Gaughan et al (2013) identified a photoperiod effect on HSP70 concentrations (r 2 = 0.94; P < 0.0001) in Angus feedlot steers. Indicating that the changes in day length, associated with the changing seasons, potentially influences the induction of the HSP response.…”
Section: Heat Shock Protein 70mentioning
confidence: 64%
“…Fader et al (1994) indicated that the induction of HSP70 in four fish species was incited by seasonal changes. Manjari et al (2015) also reported that mRNA expression of HSP70 in Tarai buffalo was twofold higher (P < 0.05) during the summer season. This indicates that the induction of the HSP response occurs at temperature thresholds to provide protection to protein structures during periods of changing climatic conditions.…”
Section: Heat Shock Protein 70mentioning
confidence: 84%
See 1 more Smart Citation
“…55 Significantly higher expression values of HSP 70 was seen in buffalo during summer season (2.37±0.12) compared to winter (0.29±0.04). 56 The association between inducible HSP70.1 single nucleotide polymorphisms (SNPs) and the HS response of peripheral blood mononuclear cells, (PBMC) was studied in dairy cows by genotyping 446 Italian Holstein cows. 33 The presence of SNPs in the 5′-UTR region of inducible HSP70 showed amelioration of heat stress response and tolerance to heat stress in bovines.…”
Section: Types Of Hsps Studied In Livestock During Hsmentioning
confidence: 99%